The Correlations among Reading Habit, Multiple Intelligences, and Writing Mastery of English Education Study Program Students of Sriwijaya University - Ayu Lestari; Sofendi Sofendi; Ismail Petrus (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
The objectives of this study were (1) to describe the students’ Reading habit, multiple intelligences, and writing mastery, (2) to find out whether or not there was significant correlation among the students’ Reading habit, multiple intelligences, and writing mastery, and (3) to find out whether or not the students’ Reading habit and multiple intelligences contributed to their writing mastery. In this study, 76 undergraduate EFL students of English Education Study Program of Sriwijaya University in the academic year 2017/2018 were chosen as a samples by means of purposive sampling. This study applied correlational research design. The data were collected by using questionnaires and test, and were analyzed by using Pearson Product Moment correlation coefficient and regression analysis. The results showed that (1) most of the students (50%) were in the average level of reading habit; most of the students (15.7%) had six dominant intelligences; most of the students (57.8%) were in the good level of writing mastery; (2) reading attitude was the only habit which had a negative and significant correlation to the students’ writing mastery (r= -271, p< 0.018); reading attitude also had positive and negative and significant correlation to the students’ ideas (r= 0.367, p< 0.001) and thesis voice audience (r= -0.236, p=< 0.040); logical intelligence was the only intelligence which had negative and significant correlation to the students’ writing mastery (r= -0.238, p= 0.038); ideas was the only the aspect of writing had a positive and significant correlation to the students’ logical intelligence (r= 0.267, p= 0.020) and intrapersonal intelligence (r= 0.250, p= 0.029); (3) reading attitude became the best predictor and influenced the students’ writing mastery with 7.3% contribution (R2 = 0.073).